Study of the Effect of Soil Type and Spraying with Anethum Graveolens Extract on the Growth and Yield of the Bean Plant Vicia Faba L - Sami Hamad Sultan (Lembaga Penelitian dan Pengabdian, Universitas Andalas, 2025)
A field experiment was conducted during the winter season of 2023–2024 in Salah Al-Din Governorate (central Iraq) to investigate the effect of soil type (loamy versus gypsiferous soils with 20% and 30% gypsum content) and foliar application of dill extract (100 ml L-1) on the growth and productivity of faba bean (Vicia faba L.). A completely randomized design (CRD) with three replications was employed, comprising a total of 12 experimental units. The results demonstrated that foliar application of dill extract at 100 ml L-1 significantly improved all studied traits compared to the control (without application). In loamy soil, the highest values were recorded for plant height (110.4 cm), root length (30.2 cm), pod length (25.2 cm), number of leaves (85 leaves plant-1), number of pods (11 pods plant-1), and number of seeds (7 seeds plant-1). In contrast, these parameters were markedly lower in the gypsiferous soils (20% and 30% gypsum content). Furthermore, loamy soil outperformed the gypsiferous soils across all indicators, confirming the decisive role of soil type in faba bean productivity. The study highlights that applying dill extract at a concentration of 100 ml L-1 in loamy soils represents a promising strategy to enhance the growth of faba bean, especially in areas with mixed or gypsiferous soils.